Strategic Lines in the Development of Printing Market Entities in the Russian Federation - V. S. Skrug; A. V. Tishkina (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The topic of the research is acute, which is envisaged by the demand for printing products in all spheres of society: political, cultural, economic, etc.   During the last decades serious changes took place on printing market, which made entities of the market revise their strategies. The article studies dynamics of printing market development and itsspecific features in the Russian Federation. The current trends on the printing service market were identified and key reasons for changing the situation on the market were investigated. The authors came to the conclusion that Russian printing houses gained serious experience in overcoming crisis situations, such as the system crisis connected with replacement of periodicals and books by e-publications and the crisis caused by COVID-19 epidemic and large-scale economic sanctions introduced in 2022. They put forward strategic lines in the development of printing market entities with regard to identified trends of market development.